Integrative study of Gerbilline rodents from anthropized areas of northern Morocco: molecular and morphometric approach - (:unkn) unknown (My University, 2020)
Gerbilline rodents represent an important component of the North African and Moroccan mammalian fauna. However, many gaps remain in the understanding of the systematics, distribution, biology, ecology and evolution of some species. In this work, we have targeted a few species of the genera Gerbillus and Meriones captured in northern Morocco and in anthropized areas. We addressed the taxonomy, systematics, phylogeny, biogeography and distribution of these species, with an integrative approach combining morphological and genetic studies. The morphological study was based on classical morphometry using 18 body and craniomandibular measurements to perform descriptive and multivariate statistical analyses. The genetic study was based on the mitochondrial DNA cytochrome b gene, which was used to calculate genetic diversity and distance, and in maximum likelihood and haplotype network analyses. For Gerbillus campestris, a potential agricultural pest, the geographical structuring of six Moroccan populations produced significant morphological differentiation and high levels of genetic divergence that allowed their discrimination into four groups. Concerning the other three species of the genus Gerbillus studied in this work (Gerbillus simoni, Gerbillus henleyi, Gerbillus amoenus), we have carried out their first genetic characterization in Morocco and we have provided additional elements concerning their taxonomy and systematics in North Africa. For the Meriones shawii/grandis species complex, reservoirs of cutaneous leishmaniasis and major agricultural pests, the geographical structuring, morphological differentiation and genetic divergence we obtained support the existence of two distinct species. Accurate characterization and reconstruction of the biogeographic history of these species will allow a better understanding of the evolution of the Gerbillinae, conservation of the more vulnerable species, and the development of more effective control strategies ag
Keywords: African Research